2016
DOI: 10.1093/mmy/myw012
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of PNA FISH®Yeast Traffic Light in identification ofCandidaspecies from blood and non-blood culture specimens: Table 1.

Abstract: PNA FISH(®) (peptide nucleic acid fluorescent in situ hybridization) Yeast Traffic Light (PNA FISH(®) YTL) assay is a commercially avaliable method for rapid identification of Candida spp. directly from positive blood cultures. This report provides a one-year experience in identification of yeasts from 25 specimens (15 positive blood cultures and 10 other clinically significant specimens) using PNA FISH(®) YTL and comparing it to VITEK 2 System. Overall, assay identification compatibility with VITEK 2 System w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Rapid diagnoses of bloodstream infections, helping physicians administer proper treatments, is essential for reducing mortality due to BSIs and sepsis, as well as reducing costs associated with hospitalized patients. Since bloodstream infections are most often caused by a single pathogenic species (monospecies infection), and only rarely caused by two or several pathogens ( Bouza et al., 2013 ), efforts have been focused on being able to skip the isolation and sub-culturing steps and analyze the positive blood cultures directly ( Ferroni et al., 2010 ; Stevenson et al., 2010 ; Radic et al., 2016 ; Salimnia et al., 2016 ; Florio et al., 2018 ; Briggs et al., 2021 ). However, the use of MALDI-TOF MS for identification of the pathogen requires in most cases, a pure culture isolate of the bacteria or fungi after observation of a positive blood culture in the cultivation step ( Opota et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Rapid diagnoses of bloodstream infections, helping physicians administer proper treatments, is essential for reducing mortality due to BSIs and sepsis, as well as reducing costs associated with hospitalized patients. Since bloodstream infections are most often caused by a single pathogenic species (monospecies infection), and only rarely caused by two or several pathogens ( Bouza et al., 2013 ), efforts have been focused on being able to skip the isolation and sub-culturing steps and analyze the positive blood cultures directly ( Ferroni et al., 2010 ; Stevenson et al., 2010 ; Radic et al., 2016 ; Salimnia et al., 2016 ; Florio et al., 2018 ; Briggs et al., 2021 ). However, the use of MALDI-TOF MS for identification of the pathogen requires in most cases, a pure culture isolate of the bacteria or fungi after observation of a positive blood culture in the cultivation step ( Opota et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The study reported assay identification compatibility of PNA FISH ® YTL with VITEK 2 System in 21/25 (84%) specimens tested, and suggested that this assay can be used to identify Candida from blood cultures, urine cultures, peritoneal fluid cultures and catheter tip cultures. [23] Although this test appears to be clinically beneficial, its use is limited due to several factors such as lack of specificity, requirement of a positive blood culture, and inability to distinguish between all clinically relevant Candida species. [21] Polymerase Chain Reaction (PCR): Is being studied to identify Candida infection in neonates more rapidly and with higher sensitivity.…”
Section: Rapid Diagnostic Methodsmentioning
confidence: 99%
“…Misidentification of uncommon Candida spp. [ 69 , 71 , 72 ] were reported, particularly C. guilliermondii . Peptide Nucleic Acid in Situ Hybridisation Yeast Traffic Light system (PNA-FISH YTL) and matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) rapidly identifies Candida spp., still only after positive blood cultures.…”
Section: Diagnostic Approachmentioning
confidence: 99%